2023
DOI: 10.1615/critrevimmunol.2023050618
|View full text |Cite
|
Sign up to set email alerts
|

Supercharged NK Cell-Based Immuotherapy in Humanized Bone Marrow Liver and Thymus (Hu-BLT) Mice Model of Oral, Pancreatic, Glioblastoma, Hepatic, Melanoma and Ovarian Cancers

Kawaljit Kaur,
Anahid Jewett

Abstract: In this paper, we review a number of <i>in vitro</i> and <i>in vivo</i> studies regarding the efficacy of supercharged NK (sNK) cell therapy in elimination or treatment of cancer. We have performed studies using six different types of cancer models of oral, pancreatic, glioblastoma, melanoma, hepatic and ovarian cancers using hu-BLT mice. Our <i>in vitro</i> studies demonstrated that primary NK cells preferentially target cancer stem-like cells (CSCs)/poorly differentiated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…The resulting Hu-BLT mouse models are well-suited for research on tumor immunotherapy ( Chuprin et al, 2023 ; De La Rochere et al, 2018 ). In addition to T cells, Hu-BLT mouse models can be used to study cancer-related NK cells, which are part of the innate immune system ( Chuprin et al, 2023 ; Kaur & Jewett, 2023 ). Notably, studies using Hu-BLT mouse models have demonstrated that human NK cells exhibit anti-tumor activity against poorly differentiated human oral squamous cells ( Kaur & Jewett, 2023 ; Kaur et al, 2018 ).…”
Section: Mouse Models For Breast Cancer Metastasis Studiesmentioning
confidence: 99%
“…The resulting Hu-BLT mouse models are well-suited for research on tumor immunotherapy ( Chuprin et al, 2023 ; De La Rochere et al, 2018 ). In addition to T cells, Hu-BLT mouse models can be used to study cancer-related NK cells, which are part of the innate immune system ( Chuprin et al, 2023 ; Kaur & Jewett, 2023 ). Notably, studies using Hu-BLT mouse models have demonstrated that human NK cells exhibit anti-tumor activity against poorly differentiated human oral squamous cells ( Kaur & Jewett, 2023 ; Kaur et al, 2018 ).…”
Section: Mouse Models For Breast Cancer Metastasis Studiesmentioning
confidence: 99%